Insight into the significance of relative humidity on Nusselt number of crossflow heat exchangers with staggered elliptic tubes. (June 2023) - Ahmed, Arshan; Hashmi, Atta ul Mannan; Butt, Fahad Rafi; Bangash, Zafar; Ghani, Shahbaz; Akhtar, Imran
Heat exchangers provide means to maintain the temperature of a system at its desired level. In this paper, numerical simulations of a heat exchanger with staggered arrangement of elliptical-shaped tubes have been performed to analyze its performance. Keeping the Reynolds number of dry and humid cooling air between 5000 and 20, 000, the impact of relative humidity on the forced convection and the average Nusselt number is analyzed for a typical radiator cross-section. Numerical results indicate an increasing trend of the Nusselt number (up to 4.5%) with relative humidity. This variation becomes more pronounced when the capacity of air to absorb water increases with the same relative humidity but at higher temperatures.